Placebo effects on kayak sprint performance in child athletes - Szabo, A. (European Journal of Sport Science, 2024)
Empirical research with adults reveals that performance-enhancing placebo effects emerge in sports and exercise. However, there is no research on children. Coaches' messages to them could have positive, performance-improving (placebo) or negative, performance-impairing (nocebo) effects. This experiment examined the former by ascribing fictive performance-enhancing properties to an ingredient of the Tic Tac mint to 12 children (aged 12.67 ± SD = 1.83 years), all elite kayakers. Another kayaker was an actor who helped enhance the credibility of the information. The children completed 2-min kayak ergometer sprints in counterbalanced control and placebo conditions. The measures included heart rate (HR), feeling state, perceived arousal, and expected- and perceived- performances. Pre-sprint and maximal HR during the sprint and distance completed in 2 minutes were statistically significantly higher (p < 0.005) in the placebo than in the control condition without being affected by order effects. While the expected performance in the placebo session was higher (p = 0.008), perceived performances did not differ statistically between the conditions. This study reveals a sport performance-related objective, but not subjective, placebo effect in children after a short kayak sprint. The findings have practical implications for performance-related messages children receive from their coaches and others and show how their altered beliefs can influence their performance.